Comparative study on the effect of initial temperatures and pressures on the laminar flame speed of the heavily carbonaceous syngas containing water vapor via reaction kinetics simulation. (8th September 2022) - Yu, Minggao; Zhai, Fuer; Li, Haitao; Han, Shixin; Li, Shanshan; Zheng, Kai; Yu, Yingying
Abstract: To study the chemical and thermodynamic effects on the laminar flame speed ( S u ) of heavily carbonaceous syngas (CO/H2 /CO2 /N2 /Air) applied in actual industries under different conditions with water addition, reaction kinetics simulation is employed by varying the ratio of CO/H2 mixture from 20:1 to 80:1 under various initial pressures and different initial temperatures. By comparing a large number of experimental data with the calculated data of six mechanisms, the most appropriate mechanism is selected to study. As for the syngas with higher carbon content, results show that the S u is more sensitive to the variation of humidity. The third-body effect of water in the key reactions H + O2 (+M) ↔ HO2 (+M) and H + OH + M ↔ H2 O + M are identified through the reaction rate evaluation and sensitivity analysis, demonstrating the unique role of HO2 radicals in the combustion of the humid heavily carbonaceous syngas. Finally, by comparing the variation of S u under different temperatures and pressures, two primary paths to generating OH radicals in heavily carbonaceous syngas are put forward. This work would provide theoretical analysis and data support for advancing the combustion efficiency of heavy-carbonaceous-related fuels in industrial manufacture. Highlights: The S u of HCS under different conditions is calculated. The reason for the variation difference of S u of wet syngas under different temperature and pressure is revealed. The importance of HO2 radical is emphasized after adding water. Two primary paths to generate OH radical is deeply analyzed.